Analisis Yuridis Pengampunan Pajak dalam Investasi di Indonesia - Agus Iskandar (KEADILAN PROGRESIF, 2017)
Tax incentives, whether tax exemptions, tax breaks, accelerated depreciation and so are different from "tax pardons". The problem in this research is how the legal form of tax forgiveness arrangement in investment in Indonesia. The problem approach in this research is the normative juridical approach that is approach by reviewing the rules related to the problem to be discussed. After data is collected and processed, then analyzed qualitatively. The result of the research shows that giving incentives in the form of debt relief and exemption of imposition of sanction give strong impetus to taxpayer to participate in tax forgiveness. For investors (old taxpayers) profits not previously / not taxable can be used to expand, or develop investment.